Collaborative dynamics in a practice of increasing utility cycling : understanding prerequisites for collaboration between bicycle planners and mobility managers in a Norwegian municipality - Clementsen Kayser, Ingvild (SLU/Dept. of Urban and Rural Development, 2019)
This study explores prerequisites for closer collaboration between practitioners who in different ways work to increase the cycle share of all travels in a Norwegian municipality. Attention is given to how practitioners make sense of the practice where they work. Within the practice, the focus is targeted at collaboration. I ask: What is characterising the practice in terms of meanings, materials and competences? What prerequisites for closer collaboration can be identified for the practice to meet the goal of increasing the cycle share of all travels? The analysis draws on practice theory and an integrative framework for collaborative dynamics. The data originate from interviews and observations with practitioners working with bicycle planning or mobility management. The results show that meaning, material and competence characterising the practice, contain prerequisites for closer collaboration in different ways. In relation to collaboration, the practitioners of the practice share meanings of making it easy and safe to cycle, benefits and challenges of closer collaboration. Material aspects related to collaboration concerns shared information and the workspace, which enable the practitioners to be updated on each other’s work. In addition, competences to ask and transmit high-quality knowledge characterise the practice in relation to closer collaboration. The study indicates that the practitioners’ relationship and shared aspirations are the main prerequisites for closer collaboration. Today, the practice in question contains little collaboration between practitioners with different work tasks, specifically bicycle planners and mobility managers. The study indicates that the practice’s capacity for joint action is limited, suggesting that a key management priority should be to enable practitioners, working with physical and social factors, to consider the knowledge they rely on and engage in closer collaboration.